Pengguatan Usaha Mikro Berbasis Potensi Lokal: Studi Kasus Desa Klungkung, Kabupaten Jember - Atik Purmiyati; Mustain; Lucy Hendrawati; Nonny Anggela; Tamat Sarmidi (Pelita Masyarakat, 2023)
During pandemic COVID-19 the number of tourist visits in East Java decreased which had an impact on the community's economy as farmers and as micro-entrepreneurs, so this study aims to encourage community economic improvement and implement the third goal of the Sustainable Development Goals (SDG's), namely increasing people's welfare by analyzing the weaknesses and strengths of community-run micro-enterprises in Klungkung Village, Jember Regency, East Java Province, using the SWOT analysis technique with IFAS and EFAS. Based on the results of IFAS and EFAS calculations which show the position of Klungkung Village in quadrant 1, it indicates that the strengths of Klungkung Village are greater than the weaknesses it has. Therefore, action is needed to maintain the position of Klungkung Village so that it remains in quadrant 1, namely by increasing its strengths and reducing its weaknesses. The SWOT results with IFAS and EFAS state that increasing strength can be done by means of product packaging technique training, digital marketing village economy training, financial reporting training, assistance in drafting village economic legality.